2014
DOI: 10.1021/bm5011646
|View full text |Cite
|
Sign up to set email alerts
|

Phage Lambda Capsids as Tunable Display Nanoparticles

Abstract: Nanoparticle technologies provide a powerful tool for the development of reagents for use in both therapeutic and diagnostic, or "theragnostic" biomedical applications. Two broad classes of particles are under development, viral and synthetic systems, each with their respective strengths and limitations. Here we adapt the phage lambda system to construct modular "designer" nanoparticles that blend these two approaches. We have constructed a variety of modified "decoration" proteins that allow site-specific mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…Lambda and P22 have been developed into powerful and versatile protein display agents, where both the head decoration proteins lambda D (Sternberg and Hoess, 1995; Mikawa et al , 1996; Nicastro et al , 2013; Chang et al , 2014) and P22 Dec (Parent et al , 2012b), as well as the lambda major tail V protein (Maruyama et al , 1994; Zanghi et al , 2007) and P22 MCP head protein (Kang et al , 2008; Servid et al , 2013) have been used successfully to display foreign peptides and proteins. Lambda virions have also been used as DNA or protein vaccine delivery vehicles in mammals (Jepson and March, 2004; Lankes et al , 2007; Clark et al , 2011; Mattiacio et al , 2011; Saeedi et al , 2014).…”
Section: The Futurementioning
confidence: 99%
“…Lambda and P22 have been developed into powerful and versatile protein display agents, where both the head decoration proteins lambda D (Sternberg and Hoess, 1995; Mikawa et al , 1996; Nicastro et al , 2013; Chang et al , 2014) and P22 Dec (Parent et al , 2012b), as well as the lambda major tail V protein (Maruyama et al , 1994; Zanghi et al , 2007) and P22 MCP head protein (Kang et al , 2008; Servid et al , 2013) have been used successfully to display foreign peptides and proteins. Lambda virions have also been used as DNA or protein vaccine delivery vehicles in mammals (Jepson and March, 2004; Lankes et al , 2007; Clark et al , 2011; Mattiacio et al , 2011; Saeedi et al , 2014).…”
Section: The Futurementioning
confidence: 99%
“…We reasoned that the shell surface density could be tuned by adjusting the ratio of wild‐type gpD and gpD‐GFP at the time of decoration. This is indeed the case and the GFP surface density can be adjusted as desired, from 0 to 100% in a controlled and defined manner (Figure ) (Chang et al, ). More importantly, the GFP‐decorated capsids are functional and DNA cargo can be packaged into the shells in vitro (Chang et al, ).…”
Section: Bacteriophage Lambda As a “Designer” Nanoparticlementioning
confidence: 97%
“…Within this context, we have demonstrated that simultaneous decoration of lambda capsids with transferrin and PEG affords particles that retain specific binding and internalization by transferrin receptor‐expressing HeLa cells, but that have attenuated nonspecific cell‐binding interactions (Koudelka & Manchester, ). Importantly, lambda capsids decorated in vitro retain biological activity and can be packaged with DNA under defined reaction conditions (Chang et al, ). These data demonstrate their potential for use as a targetable gene delivery and/or as a DNA vaccine platform whose surface can be modified in a defined manner to simultaneously optimize cell‐specific interactions and pharmacokinetic properties, and minimize antigenic potential.…”
Section: Bacteriophage Lambda As a “Designer” Nanoparticlementioning
confidence: 99%
“…Chang at al. [88]introduced the lambda capsid as a designed nanoparticle, and incorporated a variety of synthetic moieties and genetically integrated peptides, that were simultaneously displayed on the phage surface.…”
Section: Bacteriophages As Nanocarriersmentioning
confidence: 99%